Rab27a Supports Exosome-Dependent and -Independent Mechanisms That Modify the Tumor Microenvironment and Can Promote Tumor Progression - Bobrie, Angélique (2012)
During progression from single cancer cells to a tumor mass and metastases, tumor cells send signals that can subvert their tissue microenvironment. These signals involve soluble molecules and various extracellular vesicles, including a particular type termed exosomes. The specific roles of exosomes secreted in the tumor microenvironment, however, is unclear. The small GTPases RAB27A and RAB27B regulate exocytosis of multivesicular endosomes, which lead to exosome secretion, in human HeLa cells. Here, we used mouse models to show that Rab27a blockade in mammary carcinoma cells decreased secretion of exosomes characterized by endocytic markers, but also of matrix metalloproteinase 9, which is not associated with exosomes. Rab27a blockade resulted in decreased primary tumor growth and lung dissemination of a metastatic carcinoma (4T1), but not of a nonmetastatic carcinoma (TS/A). Local growth of 4T1 tumors required mobilization of a population of neutrophil immune cells induced by Rab27a-dependent secretion of exosomes together with a specific combination of cytokines and/or metalloproteinases. Our findings offer in vivo validation of the concept that exosome secretion can exert key pathophysiologic roles during tumor formation and progression, but they also highlight the idiosyncratic character of the tumor context.